Tensile properties of kenaf yarn fibre reinforced unsaturated polyester composites at different fibre orientations - Misri, Sairizal; Salit, Mohd Sapuan; Leman, Zulkiflle; Ishak, Mohamad Ridzwan (Trans Tech Publications, 2014)
This paper reported the study of tensile properties of kenaf yarn fibre reinforced unsaturated polyester (UP) composites at different fibre orientations, i.e. 0o, ±45o and 90o. It is concluded that composites with 0o orientation show higher strength and stiffness than composites with ±45o and 90o angle fibre orientation. The highest value of stress is 29 MPa for 0o loading direction followed by ±45o loading direction (28 MPa) and 90o loading direction has the lowest stress value of 6 MPa. Tensile modulus results revealed the highest value of 10.61 GPa for 0o loading direction and the tensile modulus for 45o orientation of loading direction is 5 GPa, followed by the modulus for 90o of fibre loading direction of 1.2 GPa; which is the lowest.